Avaliação da atividade anti-Acanthamoeba castellanii de frações alcaloídicas de diferentes espécies da família Amaryllidaceae e da licorina - Rosa, Maressa Dietrich (2017)
Free-living amoebae (FLA) are protozoa of wide environmental dispersion. Acanthamoeba is classified as one of the genres of FLA and can behave as an elective parasite in humans, causing two diseases: Amebic Granulomatous Encephalitis (AGE), a cronic disease of the central nervous system, difficult to treat; and Amebic Keratitis (AK), a very painful ocular cornea disease that can lead to Blindness and loss of the eyeball in more critical cases. The treatment for CA is very difficult, long, toxic and does not present complete effectiveness against existing cases. The great challenge of the treatment is the high toxicity and the resistance to the medicines. The use of plants as research sources for new amebicidal bioactive compounds has shown a good alternative; since these have high amoebicidal power and low toxicity. The objective of this study was to investigate the in vitro antiAcanthamoeba castellanii activity of 22 alkaloid enriched fractions of 12 species of Amaryllidaceae and the alkaloid lycorine on Acanthamoeba castellanii trophozoites using 3- (4,5-dimethyl) 5-diphenyltetrazolium (MTT). Chlorhexidine 0.02% was used as a positive control. The species Hippeastrum canastrense, Hippeastrum dinizcruziae, Crinum giganteum Hippeastum puniceum and lycorine showed a concentration-dependent effect, with H. canastrense and H. diniz-cruziae at the concentration of 2000 μg.mL-1, with a high amebicide (100% Inhibition) greater than chlorhexidine (86% inhibition). The cytotoxicity of these fractions and the lycopene were also evaluated on MDCK mammalian cells by the use of the MTT dye and showed a concentration-dependent effect, and H. diniz-cruziae at concentrations of 250, 500 and 1000 μg.mL-1 showed low cytotoxicity (5 to 7% inhibition) less than chlorhexidine (97% inhibition). The IC50 value calculated for H. canastrense, H. dinizcruziae, Crinum giganteum, H. puniceum and lycorine was from 285.61 to 962.75 μg.mL-1 and the selectivity index (SI) was 1, 27 to 7.0. The H. diniz-cruziae species presented promising results, with high amebicidal power (100% inhibition), low cytotoxicity (5 to 7% inhibition), lower IC50 value of 285.61 μg.mL-1 and higher IS value (7,0), being a promising target for the discovery of new drugs with antiAcanthamoeba castellanii activity.